FLEXIBLE AND ADAPTIVE BUILDINGS SINCE EARLY DESIGN STAGE - Andrade, Joana; Castro, Maria de Fátima; Bragança, Luís (Encontro Latino-americano e Europeu sobre Edificações e Comunidades Sustentáveis (euroELECS), 2023)
The sustainability concept implies a long-term vision. People's life is constantly changing, and buildings should cope with it. Buildings should be able to adapt to new requirements whenever needed. Nevertheless, conventional buildings are not design do be modified, leading to unnecessary and premature demolition. Preserving built heritage, promotes the population wellbeing and cultural identity. Thus, a building's flexibility potential can have major impact on society, environment, and economy. In this since, building design should include flexibility concerns to allow buildings to adjust to new requirements easily, hence extending their life cycle. The concept of adaptability is already considered in several building sustainability assessment (BSA) tools; however, it is not common practice, nor meant to all types of buildings. In addition, existing BSA tools are only applicable to later design stages not being able to aid designers establish and accomplish adaptability goals. In this sense, this paper aims at presenting a method to support decision-making at early design stages, fulfilling this gap, by describing how adaptability can be ascribed in BSA tools at early design. The method allows establishing objectives and comparing alternative design solutions to support electing the solution with the better performance, regarding the established goal. It was found that the method should include the following two sub-indicators regarding adaptability: (i) flexibility provision and (ii) adaptability capacity. The first, deals with design strategies to accommodate change, through the transformation capacity, while the second quantifies the space availability for change, following the open building concept, evaluating the percentage of adaptable area. When considered at early design, these aspects allow extending the buildings” life cycle, reducing their environmental impact. Increased transformation capacity means that buildings can better accommodate new requirements, improve their dismantling potential, thus enabling replacement, reuse, or recycling towards sustainable and resilient buildings.